THE DEVELOPMENT OF E-PARTOGRAPH MODULE AS A LEARNING PLATFORM FOR MIDWIFERY STUDENTS: THE ADDIE MODEL - Selasih Putri Isnawati Hadi; Tjahjono Kuntjoro; Sri Sumarni; Muh.Choiroel Anwar; Melyana Nurul Widyawati; Rr.Sri Endang Pujiastuti (Belitung Raya Foundation, Indonesia, 2017)
To enhance the competencies of midwifery students, one must design a learning instruction in such a manner that it will optimize the learning. The learning materials designed based on technology will facilitate the learners to achieve the desired outcome. In this study, e-partograph was developed using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instruction model. The module of e-partograph was followed the structural guideline of Department of National Education of Indonesia consisted of: self-instruction, self-contained, stand alone, adaptive, and user friendly. The evaluation showed that e-partograph was feasible (99.3) in the material subject, very feasible (195) in terms of media, feasible (101.6) in the try-out, and feasible for the students (users) (104.18). It is suggested that e-partograph could be applied in the teaching learning system, and it is expected to contribute positively to the increase in skill and competence of midwifery students who will be able to carry out its role both academic and practice.